Beyond 50: ASEAN’s Role in the Evolving Regional Order - Han, David (2017)
Given the flurry of activities surrounding ASEAN’s commemoration of its 50th anniversary last month, it is now timely to take a step back, reflect on ASEAN’s achievements and then look ahead to its future. Will the organisation’s flexibility in meeting future geo-political, security, social, and economic challenges ensure its centrality in the evolving regional order?